Perilaku Belajar Siswa di Lingkungan Penambangan Emas Ilegal: Studi Kualitatif di SMP Negeri 3 Banama Tingang - Ardy Wiranata; Abustan Abustan; Rinto Alexandro (Jurnal Ilmiah Kanderang Tingang, 2026)
This study aims to analyze the learning behavior of students living in an illegal gold mining (IGM) environment in the Kahayan River Basin area, particularly at SMP Negeri 3 Banama Tingang. Illegal gold mining activities that have developed within the community not only affect social and economic conditions but also influence students’ behavior and educational orientation. This study employed a qualitative approach using a descriptive research design. The research informants consisted of 17 students, 5 parents, 5 teachers, and 5 community leaders selected through purposive sampling techniques. Data were collected through in-depth interviews, observations, and documentation. Data analysis was conducted using the Miles, Huberman, and Saldaña model, which includes data reduction, data display, and conclusion drawing. Data validity was tested through source triangulation and technique triangulation. The findings revealed that the illegal gold mining environment negatively affects students’ learning motivation, discipline, attendance rates, and learning concentration due to non-conducive environmental conditions. In addition, parental involvement in supporting children’s education remains relatively low because parents are more focused on mining activities. A social environment that prioritizes instant economic gains causes some students to perceive formal education as a secondary need. This study concludes that illegal gold mining activities in the Kahayan River Basin influence students’ learning behavior through social, economic, family, and community environmental factors.